SYNTHESIS OF STRUCTURAL CONTROL ON RESERVOIR DISTRIBUTION WITHIN SEPINGGAN CARBONATE SEQUENCE, MANPATU FIELD, SOUTH MAHAKAM, KUTAI BASIN - Wuryanto, Argo
The M-1x exploration well has confirmed its discovery with initial targets in the Sepinggan Deltaic Sequences (SDS) interval, as well the presence of hydrocarbons in the shallow part known as the Sepinggan Carbonate Sequences (SCS). Siliciclastic reservoirs in this interval have not been explored within Mahakam PSC as it previously renown as proven losses carbonate intervals. This paper aims to map the distribution of siliciclastic reservoir at SCS interval, dan to reconstruct the geological structure to define the genesis and factors controlling the distribution and sedimentation of siliciclastic reservoirs. Drill stem test (DST) has confirmed property and the extension of a mixed siliciclastic-carbonate reservoir. Although SCS interval comprises of carbonate reefs and platforms, the focus of this study is on siliciclastic layers, which are mainly deposited as stacked sand bars occasionally interspersed with channel formation across the shelf. Simultaneous inversion along with some seismic attributes, such as variance, sweetness, and spectral decomposition, were generated to provide thorough understanding the genetic and relation of fault bounded siliciclastic distribution. 3D Geomodel derived from seismic, well data and sedimentological concept is used to enable and visualized the relation between fault and siliciclastic distribution. 3D reconstruction is provided to show the relation between fault and siliciclastic sedimentation. The reconstruction emphasizes the existence of sedimentation pathways along the fault and channel between carbonates. Beside topography, ocean circulation controls sediment orientation, and eustasy provides influence on sediment supply.